Predictors of Technostress Level Among Intermediate Pupils - Sara Jane Cruz; Germellee Michael Cruz; Julius Meneses (Diversitas Journal, 2025)
Current changes in the educational modalities that were brought by the pandemic have created different effects among the school’s stakeholders, especially with the learners who are the first and foremost constantly being exposed to it. St. Paul College Pasig being one of the pioneers in using educational technologies, though seem to be prepared with the changes in the modalities, is still experiencing challenges in creating a caring environment in online learning. It is from this standpoint that the researchers aimed to discover the effect of online learning and the use of technology in pupils’ technostress. In this study, the researchers tapped 250 Grades 4-6 pupils to represent the whole population of the intermediate pupils in the Grade School Department. Using stratified random sampling technique, 250 pupil-respondents were involved. This includes 74 pupils in Grade 4, 88 pupils in Grades 5, and 88 pupils in Grade 6. Guided by the predictive correlational design, the researchers gathered data from the respondents using contextualized technostress questionnaires of Tarafdar et al. (2007) and Wang (2020) with a Cronbach alpha reliability of 84 and 83, respectively. Result mean scores were tallied and analyzed revealing that the Grades 4-6 pupils are experiencing only low technostress level according to the interpretation index of Ahmad (2010). Subsequently, the results were also further analyzed using multiple linear regression to reveal which predictor affects the pupils’ technostress the most. This statistical treatment revealed that for both Grades 4 and 5, Techno-invasion has the most effect on the pupil-respondents’ technostress with 70.2% for Grade 4 and 121.2% for Grade 5. On the other hand, regression analysis for the Grade 6 respondents reflected statistically non-significant p-values. This means that there is not enough evidence to solidify any claim and results might have happened by chance.